2016
DOI: 10.13189/adm.2016.040403
|View full text |Cite
|
Sign up to set email alerts
|

In-silico Structure Modeling and Docking Studies Using Dipeptidyl Peptidase 4 (DPP4) Inhibitors against Diabetes Type-2

Abstract: Recently recognized class of oral hypoglycemic, dipeptidyl peptidase (DPP4) inhibitors could block the dipeptidyl peptidase 4 (DPP4) enzymes. DPP4 is an intrinsic membrane glycoprotein and a serine exopeptidase that plays a major role in glucose metabolism and responsible for the degradation of incretins such as GLP-1, therefore providing a useful treatment to diabetes mellitus type 2. The present work focused on the study of the structural homology modeling of dipeptidyl peptidase 4 [Homo sapiens] (NP_001926)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Construction of a high-quality benchmark data set is the foundation for the development of a robust and reliable predictor. In this study, the experimentally validated DPP-IV inhibitory peptides were extracted from the literature ,, and publically available databases (i.e., BIOPEP-UWM), and these peptides were unique and considered as the positive data sets. Since there are very few experimentally proven non-DPP-IV inhibitory peptides, we employed random unique peptides without DPP-IV inhibitory activity and an equal number of positive data set from various literatures. ,, Here, we assigned these random peptides as the negative data sets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Construction of a high-quality benchmark data set is the foundation for the development of a robust and reliable predictor. In this study, the experimentally validated DPP-IV inhibitory peptides were extracted from the literature ,, and publically available databases (i.e., BIOPEP-UWM), and these peptides were unique and considered as the positive data sets. Since there are very few experimentally proven non-DPP-IV inhibitory peptides, we employed random unique peptides without DPP-IV inhibitory activity and an equal number of positive data set from various literatures. ,, Here, we assigned these random peptides as the negative data sets.…”
Section: Methodsmentioning
confidence: 99%
“…Their results demonstrated that the physicochemical properties (i.e., molecular weight, bulkiness, and an increasing number of carbon and hydrogen atoms of amino acids forming the sequences) of the peptides play crucial roles in the bitterness of the peptides. Until now, several QSAR studies and methods have been made on this aspect. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandit and Pandey [1]; Awasthi et al [2] proposed that diabetes mellitus is a multi-factorial metabolic disorder and forthcoming epidemic all over the globe that caused due to ineffective secretion of insulin. Prajapat and Bhattacharya [3]; Zhaolan et al [4] proposed that diabetic patient numbers will possibly rise up to 300 million by 2025 in India. Seyed Hosseini et al [5] and Rahman Hassan et al [6] also estimated that 346 million diabetic patients will be increase up to 439 million in 2030 worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is metabolic epidemic that occur due to ineffective secretion of insulin from pancreas [1,2] and the possibly the worldwide number of diabetic patient will be rise up to 439 million by 2030 [3,4]. Vitamin E supplementation could improve glycemic control in diabetes patients [5,6].Vitamin C supplementation is effective in prevention of non-enzymatic glycosylation of proteins [7] and it also serves as therapeutic agent for diseases that protects body from damage caused by free radicals [8].…”
Section: Introductionmentioning
confidence: 99%